Cross-species comparisons reveal resistance of human skeletal stem cells to inhibition by non-steroidal anti-inflammatory drugs - Goodnough, L. Henry; Ambrosi, Thomas H.; Steininger, Holly M.; Butler, M. Gohazrua K.; Hoover, Malachia Y.; Choo, HyeRan; Van Rysselberghe, Noelle L.; Bellino, Michael J.; Bishop, Julius A.; Gardner, Michael J.; Chan, Charles K. F. (Frontiers in Endocrinology, 2022)
Fracture healing is highly dependent on an early inflammatory response in which prostaglandin production by cyclo-oxygenases (COX) plays a crucial role. Current patient analgesia regimens favor opioids over Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) since the latter have been implicated in delayed fracture healing. While animal studies broadly support a deleterious role of NSAID treatment to bone-regenerative processes, data for human fracture healing remains contradictory. In this study, we prospectively isolated mouse and human skeletal stem cells (SSCs) from fractures and compared the effect of various NSAIDs on their function. We found that osteochondrogenic differentiation of COX2-expressing mouse SSCs was impaired by NSAID treatment. In contrast, human SSCs downregulated COX2 expression during differentiation and showed impaired osteogenic capacity if COX2 was lentivirally overexpressed. Accordingly, short- and long-term treatment of hSSCs with non-selective and selective COX2 inhibitors did not affect colony forming ability, chondrogenic, and osteogenic differentiation potential in vitro. When hSSCs were transplanted ectopically into NSG mice treated with Indomethacin, graft mineralization was unaltered compared to vehicle injected mice. Thus, our results might contribute to understanding species-specific differences in NSAID sensitivity during fracture healing and support emerging clinical data which conflicts with other earlier observations that NSAID administration for post-operative analgesia for treatment of bone fractures are unsafe for patients.